2019
DOI: 10.1038/s41401-019-0314-9
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 attenuates high glucose-induced apoptosis in proximal renal tubular cells by inhibiting the JNK/Bim pathway

Abstract: Proximal renal tubular damage is a critical process underlying diabetic kidney disease (DKD). Our previous study shows that prostaglandin E1 (PGE1) reduces the apoptosis of renal tubular cells in DKD rats. But its underlying mechanisms remain unclear. In this study we investigated the protective effects of PGE1 in DKD rats and high glucose (HG, 30 mM)-treated HK-2 proximal tubular cells. Four weeks after uninephrectomized streptozotocin-induced diabetic rats were established, the DKD rats were administered PGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Moreover, TUNEL analysis was used to further analyze the degree of cell damage in kidney tissues and the results indicated that apoptosis responses were observed signi cantly in PM 2.5 exposed rats. Previous studies suggested that apoptosis in renal tubular cells was considered as a causal factor in the development of kidney diseases/injury (Song et al, 2018;Zhang et al, 2019). Many in vivo and in vitro experiments have con rmed that PM 2.5 induced inappropriate apoptosis (too much) is one of the potential mechanisms of PM 2.5 health hazards (Liu et al, 2019;Wang et al, 2017b;Zhang et al, 2018a;Zhou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TUNEL analysis was used to further analyze the degree of cell damage in kidney tissues and the results indicated that apoptosis responses were observed signi cantly in PM 2.5 exposed rats. Previous studies suggested that apoptosis in renal tubular cells was considered as a causal factor in the development of kidney diseases/injury (Song et al, 2018;Zhang et al, 2019). Many in vivo and in vitro experiments have con rmed that PM 2.5 induced inappropriate apoptosis (too much) is one of the potential mechanisms of PM 2.5 health hazards (Liu et al, 2019;Wang et al, 2017b;Zhang et al, 2018a;Zhou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lipofectamine 2000 was used to transfect miR-483-5p mimic or inhibitor when the cells grew to the logarithmic growth phase. After transfection for 6 hours, the cells were stimulated by replacing the medium containing high glucose (HG, 30 mM glucose) for 24 hours for subsequent experiments [22]. The normal glucose concentration of 5.5 mM glucose was used in the control group, and 5.5 mM glucose added 24.5 mM mannitol as the high osmotic (HO) pressure solution group.…”
Section: E L L Culture and Transfectionmentioning
confidence: 99%
“…Anisomycin was known to induce cell death and JNK activation was required for Anisomycin induced apoptosis ( Zhou et al, 2019 ; Zhang et al, 2020 ). We examined the p-JNK expression by western blot after the treatment of anisomycin in human breast cancer cell lines (MDA-MB-231, MDA-MB-436, BT549, Hs578T).…”
Section: Resultsmentioning
confidence: 99%